PENGARUH BIOCHAR TERHADAP BEBERAPA SIFAT KIMIA TANAH DAN PERTUMBUHAN TANAMAN NILAM (Pogostemon cablin Benth) PADA TANAH TAMBANG NIKEL - Mbay, Wa Ode Nurmahsita; Darwis, Darwis; Resman, Resman; Ginting, Sahta; Syaf, Hasbullah; Namriah, Namriah (Jurnal Agroteknologi (Agronu), 2023)
The purpose of this study is to know the effect of application of rice husk biochar on changes in soil chemical properties and the growth of patchouli plants (Pogestemon cablin Benth). The research was conducted at Field Laboratory II, Faculty of Agriculture, Halu Oleo University in October-December 2022. This study used a Randomized Block Design (RBD) consisted of 6 treatments biochar, which are B0 = without biochar (control), B1 = 75 g polybag-1, B2 = Biochar 150 g polybag-1, B3 = 225 g polybag-1, B4 = 300 g polybag-1, B5 = 375 g polybag-1. The results showed that biochar increase soil pH from 5.76 to 6.57, CEC from 22.79 me 100 g-1 to 39.36 me 100 g-1, Available-P from 4.71 ppm to 13.04 ppm, Organic-C from 0.20% to 1.08%, and in constrast reduced Ni content from 776.10 ppm to 234.93 ppm, Fe from 6433.53 ppm to 3450.93 ppm. The application of rice husk charcoal affected significantly , the plant height, number of leaves and dry weight of plants. Biochar application up to 300 g polybag-1 (B4) is the most efficient dose to increase patchouli plant growth on nickel mine soil.Keywords: Biochar, ex- Nickel mining soil, Patchouli plant, soil chemical properties.